Towards a Model of Community co-curation in the Caribbean: : Community of Curatorial Practice at the Barbados Museum & Historical Society - Hall, Kaye; McGuire-Batson, Natalie (Culture Caleidoscoop, 2023)
In 2018, The University of the West Indies and The Barbados Museum & Historical Society embarked on a project to facilitate a community-led composite history of the Caribbean migratory experience to Britain. This was the Museum’s first attempt at an intentional large scale community collaboration across the diaspora. The resulting outputs - the Virtual Museum of Caribbean Migration and Memory and The Enigma of Arrival: The Politics and Poetics of Caribbean Migration to Britain, a rare Caribbean-based travelling exhibition on post-war migration from the Caribbean territories to Britain and the subsequent post-independence rejection of Caribbean migrants, and the process which generated them, are models for how Caribbean museums with global communities and audiences can incorporate an inclusive practice model. This paper chronicles how the museum has evolved from small community interventions and collaborations to this major project as examples of a “community of curatorial practice” (Lave and Wenger, 1991) and explores next steps for imagining the truly inclusive museum in our curatorial practice going forward.